(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
Sesame is an important oil crop in the world, which is grown mainly to obtain its seeds rich in oil, protein, calcium and phosphorus, which is used to make Tahini and Halawa tahini, with high nutritional value, because it contains calcium, proteins, fats, sugars and vitamin E, This research has sought to achieve the following: • Calculate and analyze the productive costs of grinding Sesame and packing its products in Lattakia and Tartous governorates. • Economic evaluation of grinding sesame and packing its products in Lattakia and Tartous governorates through calculation of economic analysis indicators. It was found through the study of economic efficiency indicators for grinding sesame and packing its products in the governorates of Lattakia and Tartous that: The net productive income of the studied sample amounted to (217.6) Million SP / year, the annual profit realized (198.7) Million SP / year, gross margin is equivalent to (218.5) Million SP / year, industrial production efficiency reached (2.05), economic efficiency reached (1.88). يعد السمسم من المحاصيل الزيتية الهامة في العالم، والتي تزرع أساساً للحصول على بذوره الغنية بالزيت والبروتين والكالسيوم والفوسفور، والتي تستخدم لصناعة الطحينة والحلاوة الطحينية، ذات القيمة الغذائية العالية، وذلك لاحتوائها على الكالسيوم والبروتينات والدهون والسكريات وفيتامين E، وقد سعى هذا البحث إلى تحقيق الأهداف الآتية: أ‌- حساب التكاليف الإنتاجية لطحن السمسم وتعبئة منتجاته في محافظتي اللاذقية وطرطوس وتحليلها. ب‌- التقييم الاقتصادي لطحن السمسم وتعبئة منتجاته في محافظتي اللاذقية وطرطوس، من خلال حساب مؤشرات التحليل الاقتصادي. وقد تبين من خلال دراسة مؤشرات الكفاءة الاقتصادية لطحن السمسم وتعبئة منتجاته في محافظتي اللاذقية وطرطوس أن: صافي الدخل الإنتاجي للعينة المدروسة بلغ (217.6) مليون ل.س/سنة، الربح السنوي المحقق يعادل (198.7) مليون ل.س/سنة، الهامش الإجمالي يعادل (218.6) مليون ل.س/سنة، الكفاءة الإنتاجية التصنيعية بلغت (2.05)، الكفاءة الاقتصادية بلغت (1.88).